GAMBARAN POLA MAKAN DAN STATUS GIZI PADA PRA LANSIA DAN LANSIA DI NAGARI SUMANIAK KABUPATEN TANAH DATAR - Negara, Haegha Satya; Firdawati, Firdawati; Windasari, Noverika; Mulyana, Roza; Welan, Rahmani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: The elderly are generally sixty years old and above, experiencing the aging process which results in a decrease in physical function and has an impact on quality of life which can be seen from diet. A healthy diet is important for the health of the elderly, which is reflected in nutritional status. This study aims to determine the description of diet and nutritional status in pre-elderly and elderly people in Nagari Sumaniak, Tanah Datar Regency. Objective: The purpose of this study was to determine the description of diet and nutritional status in pre-elderly and elderly people in Nagari Sumaniak, Tanah Datar Regency. Methods: This type of research is descriptive with a cross sectional design and total sampling technique. The research sample totalled 40 respondents obtained from secondary data from community service results in October 2021 using the Food Frequency Questionnaire and Body Mass Index values. Results: The results showed that most of the respondents were aged 60-74 years which fell into the elderly category (52.5%). Most of the respondents were female (72.5%) with the last level of education in elementary school (32.5%) and still working (87.5%). The description of diet mostly has a good diet (57.5%) and nutritional status in the obesity category (40%). Conclusion: The conclusion of this study is that most respondents have a good diet but are classified as obese. Advice to health workers to prioritise the promotion and prevention of groups at risk of obesity and poor diet.baik.